Mobilizing the role of local foods in rural destination: opportunities and challenges in community development - Abdul Raji, Mohd Nazri; Abdul Karim, Muhammad Shahrim; Che Ishak, Farah Adibah; Arshad, Mohd Mursyid (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Many past literatures acknowledge that tourism industry in rural destination has generates various economic benefits to the local communities. In tourism aspects, rural destinations tend to sell common attributes such as nature, historical sites, natural landscape and cultural heritage. Current research has found that local food at the rural destination helps to promote destination awareness, form destination identity, create tourist activity and contribute to tourist satisfaction and experience. Local food in rural destination not only satisfy hunger, but also provides a major component of intangible heritage and become increasingly important attraction for tourists. By participating in local food activities, it gives the opportunity to identify closely the different culture and identity of a rural destination. Integrating rural destination and local food system provides new opportunities for the local communities to increase economic development, promote the cultural heritage and respond to the demand for unique dining experience. Thus, local food can be used as a tool to developed economies in rural destination. Therefore, this conceptual paper provides the understanding of the benefits that local food provides to local communities particularly at rural destinations.